1999
DOI: 10.1086/307727
|View full text |Cite
|
Sign up to set email alerts
|

A Multicloud Warm‐Absorber Model for NGC 4051

Abstract: A multi-cloud model is presented which explains the soft X-ray excess in NGC 4051 and, consistently, the optical line spectrum and the SED of the continuum. The clouds are heated and ionized by the photoionizing flux from the active center and by shocks. Diffuse radiation, partly absorbed throughout the clouds, nicely fits the bump in the soft X-ray domain, while bremsstrahlung radiation from the gaseous clouds contribute to the fit of the continuum SED. Debris of high density fragmented clouds are necessary t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…Veilleux (1991) reported blue wings in the forbidden optical emission lines and proposed a model with outflow and obscuring dust. The mid‐ and far‐infrared fluxes have been explained by Rodriguez Espinosa et al (1996) and Contini & Viegas (1999) as due to hot dust emission. In X‐rays Lawrence et al (1985) found variability on time‐scales of hundreds of seconds and Salvati et al (1993) reported a flux change by a factor of 2 at 2.2 μm in 6 months.…”
Section: Samplementioning
confidence: 80%
“…Veilleux (1991) reported blue wings in the forbidden optical emission lines and proposed a model with outflow and obscuring dust. The mid‐ and far‐infrared fluxes have been explained by Rodriguez Espinosa et al (1996) and Contini & Viegas (1999) as due to hot dust emission. In X‐rays Lawrence et al (1985) found variability on time‐scales of hundreds of seconds and Salvati et al (1993) reported a flux change by a factor of 2 at 2.2 μm in 6 months.…”
Section: Samplementioning
confidence: 80%
“…However, there may be other models which explain the observed line ratios of NGC 4051. Recently, Contini & Viegas (1999) proposed a multi-cloud model in which the existence of shocks is introduced for NGC 4051. Their model explains the optical line ratios and the continuum SED, although they did not mention the spatial extension of ionized regions.…”
Section: Resultsmentioning
confidence: 99%
“…The data at ν ≤ 10 15 Hz show that contribution from the old stellar population is present in Ark 564 (dash-dot line), as is found for most AGN. In the radio band, only one measurement in one frequency is available, so we cannot decide whether there is also some contribution from synchrotron emission created by Fermi mechanism at the shock front (dashed line, see Contini & Viegas 1999). …”
Section: The Sed Of the Continuummentioning
confidence: 99%